How far from the gold standard? Comparing the accuracy of a Local Position Measurement (LPM) system and a 15 Hz GPS to a laser for measuring acceleration and running speed during team sports - Fischer-Sonderegger, K.; Taube, W.; Rumo, M.; Tschopp, M. (PLOS ONE, 2021)
Purpose: This study compared the validity and inter- and intra-unit reliability of local (LPM) and global (GPS) position measurement systems for measuring acceleration during team sports. Methods: Devices were attached to a remote-controlled car and validated against a laser. Mean percentage biases (MPBs) of maximal acceleration (amax) and maximal running speed (vmax) were used to measure validity. Mean between-device and mean within-device standard deviations of the percentage biases (bd-SDs and wd-SDs) of amax and vmax were used to measure inter- and intra-unit reliability, respectively. Results: Both systems tended to underestimate amax similarly (GPS: -61.8 to 3.5%; LPM: -53.9 to 9.6%). The MPBs of amax were lower in trials with unidirectional linear movements (GPS: -18.8 to 3.5%; LPM: -11.2 to 9.6%) than in trials with changes of direction (CODs; GPS: -61.8 to -21.1%; LPM: -53.9 to -35.3%). The MPBs of vmax (GPS: -3.3 to -1.0%; LPM: -12.4 to 1.5%) were lower than those of amax. The bd-SDs and the wd-SDs of amax were similar for both systems (bd-SDs: GPS: 2.8 to 12.0%; LPM 3.7 to 15.3%; wd-SDs: GPS: 3.7 to 28.4%; LPM: 5.3 to 27.2%), whereas GPS showed better bd-SDs of vmax than LPM. Conclusion: The accuracy depended strongly on the type of action measured, with CODs displaying particularly poor validity, indicating a challenge for quantifying training loads in team sports.